Vesivirus 2117 capsids more closely resemble sapovirus and lagovirus particles than other known vesivirus structures - Conley, Michaela; Hansman, Grant S. (Journal of general virology, 2017)
Vesivirus 2117 is an adventitious agent that, in 2009, was identified as a contaminant of Chinese hamster ovary cells propagated in bioreactors at a pharmaceutical manufacturing plant belonging to Genzyme. The consequent interruption in supply of Fabrazyme and Cerezyme (drugs used to treat Fabry and Gaucher diseases, respectively) caused significant economic losses. Vesivirus 2117 is a member of the Caliciviridae, a family of small icosahedral viruses encoding a positive-sense RNA genome. We have used cryo-electron microscopy and three-dimensional image reconstruction to calculate a structure of vesivirus 2117 virus-like particles as well as feline calicivirus and a chimeric sapovirus. We present a structural comparison of several members of the Caliciviridae, showing that the distal P domain of vesivirus 2117 is morphologically distinct from that seen in other known vesivirus structures. Furthermore, at intermediate resolutions, we found a high level of structural similarity between vesivirus 2117 and Caliciviridae from other genera: sapovirus and rabbit hemorrhagic disease virus. Phylogenetic analysis confirms vesivirus 2117 as a vesivirus closely related to canine vesiviruses. We postulate that morphological differences in virion structure seen between vesivirus clades may reflect differences in receptor usage.